Do insectivorous bird communities decline on land-bridge forest islands in Peninsular Malaysia? - Yong, Ding Li; Qie, Lan; Sodhi, Navjot S.; Koh, Lian Pin; Peh, Kelvin S.-H.; Lee, Tien Ming; Lim, Haw Chuan; Lim, Susan Lee Hong (Cambridge University Press, 2011)
To assess the impact of habitat fragmentation on tropical avian communities, we sampled lowland forest birds on six land-bridge islands and two mainland forest sites in Lake Kenyir, Peninsular Malaysia using timed point counts, hypothesizing that insectivorous birds are the worst affected guild. We used an information-theoretic approach to evaluate the effects of area, isolation, primary dietary guild (omnivore, frugivore and insectivore) and their interactions in predicting species richness, abundance and diversity. Our analysis showed that a model that considered the effects of area, dietary guild and their interaction best explained observed patterns of species richness. But a model considering both area and dietary guild best explained the variation in abundance. Notably, insectivorous birds were singled out as the dietary guild most sensitive to fragmentation, followed by frugivorous and omnivorous birds and hence provide support for our hypothesis. Assemblages of insectivorous birds were clearly depauperate on anthropogenic forest islands in Lake Kenyir and are consistent with forest fragmentation studies in the Neotropics. Given their specialized foraging ecology and diversity, conservation of intact communities of insectivorous bird guilds in Malaysia will be critical for maintaining predator-prey interactions in lowland tropical forests. © 2010 Cambridge University Press.